2015
DOI: 10.1007/s11442-015-1227-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal differences and convergence of urban industrial land use efficiency for China’s major economic zones

Abstract: Based on an SBM model, this paper first analyzes the spatial differences of urban industrial land use efficiency (UILUE) in the six main economic zones of China. Then, we analyze the dynamic changes in the urban industrial land's total factor productivity (UILTFP) by using the Malmquist productivity index approach, and we examine the UILTFP's convergence. The results show that the Pearl River Delta and the Yangtze River Delta have a higher UILUEs but show downward trends in UILTFPs. The other four zones, Beiji… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 11 publications
3
36
0
Order By: Relevance
“…Therefore, strengthening environmental regulations on local governments and enterprises, developing low carbon industries and promoting the use of clean energy would be helpful to improve the NLCPIL. This is consistent with the findings of Xie et al [9].…”
Section: Determinants Of the Nlcpilsupporting
confidence: 94%
See 2 more Smart Citations
“…Therefore, strengthening environmental regulations on local governments and enterprises, developing low carbon industries and promoting the use of clean energy would be helpful to improve the NLCPIL. This is consistent with the findings of Xie et al [9].…”
Section: Determinants Of the Nlcpilsupporting
confidence: 94%
“…Therefore, the regional gaps in TCPIL seem to be narrowing, which is helpful for realizing the balanced and sustainable utilization of industrial lands in China. This is consistent with the findings of Xie et al, which reached a similar conclusion at both the provincial and city levels [9].…”
Section: Nlcpil and Its Decompositionssupporting
confidence: 93%
See 1 more Smart Citation
“…Many scholars have conducted a convergence analysis of efficiency values; for example, Xie analyzed the convergence of TFP of industrial land in China's six major economic zones. The study found that each economic zone converged to its own steady-state level [30]. Li analyzed the convergence of the TFP of agriculture from 1985 to 2005 and found that China's agricultural productivity has convergence [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most industrial enterprises are labor-intensive and engaged in low-tech production activities because of cheap labor. This inevitably impedes the large-scale use of new technologies and industrial upgrading, and negatively affects the PIGD [37]. Further, many studies suggested that China had entered a middle or late stage of industrialization, which implyies that China's industrial development will shift from a simple emphasis on economic output to improvements in the quality of industrial development [38].…”
Section: Influencing Factorsmentioning
confidence: 99%